Colloquial Words Used in "Gossip Girl" Drama Script Written by Cecily Von Ziegesar - Hardianti, Meliana; Hartono, Hartono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2017)
An Analysis of the Language Style Used by Barrack Obama and Michelle Obama in Oprah Winfrey Show